Indigenous liberation theology and spirituality looking to the past for answers in the present - Nadeau, Kathleen; Fung, Jojo M. (2018)
Pope Francis's Laudato si': On the Care of Our Own Common Home offers a framework for dealing with poverty, ecological degradation, and climate change in the Philippines. His interconnected and holistic ecological spirituality shares some commonalities with indigenous spirituality shares some commonalities with indigenous spirituality where the earth is a gift from God to be taken care of - not taken advantage of or taken for granted. In this paper, we explore how this integrated approach of indigenous spirituality and liberation theology offers some long-term solutions to the problems of poverty and climate- change. Taking the position of being politically engaged in the world accords well with indigenous spirituality, this political engagement is thereby defined by loving and taking care of all of God's creation. Diametrically opposing this political engagement to political opportunism- attempts to maintain power and influence without regard for ethical or political principles - views human and non-human sentient animals and all living life forms as interconnected and sacred. A brief explanation of climate change in the Philippine context suggests the idea of rekindling a love for "earth houses" - a term earlier coined by the Egyptian architect, Hassan Fathy (1900-1989). Fathy envisioned earth homes as an affordable way to house the poor, heal, and give new life to the natural environment.
Keywords: Climate change; Sustainable development; Liberation theology